93.9k views
1 vote
Simplify (x+2)(x+6) using grouping and write the resulting expression in standard form

User Pham Trung
by
4.9k points

2 Answers

5 votes

Answer:

x2 + 8x + 12

Explanation:

(x + 2) (x + 6) = x (x + 6) + 2 (x + 6)

= x * x + 6x + 2 (x + 6)

= x2 + 6x + 2 (x + 6)

= x2 + 6x + 2x + 2 * 6

= x2 +6x + 2x + 12

= x2 + 8x + 12

User Fmorency
by
4.8k points
4 votes

Explanation:

x2+6x+2x+12

x(x+6)2(x+6)

(x+2)(x+6)

i don't know if I understood what you were looking for,anyway I hope it helps

User Dysosmus
by
5.1k points